Managing severe acute respiratory syndrome (SARS) intellectual property rights: the possible role of patent pooling - James H.M. Simon; Eric Claassen; Carmen E. Correa; Albert D.M.E. Osterhaus (The World Health Organization, 2005)
Patent applications that incorporate the genomic sequence of the severe acute respiratory syndrome (SARS) coronavirus, have been filed by a number of organizations. This is likely to result in a fragmentation of intellectual property (IP) rights which in turn may adversely affect the development of products, such as vaccines, to combat SARS. Placing these patent rights into a patent pool to be licensed on a non-exclusive basis may circumvent these difficulties and set a key precedent for the use of this form of mechanism in other areas of health care, leading to benefits to public health.